Component analyses and their implication on the breeding of soya bean (Glycine max (L.) Merr) - O. J., Ariyo (Universiti Putra Malaysia Press, 1995)
The characters associated with seed yield in 20 genotypes of soya bean, Glycine max (L) Merr. were analysed using techniques of correlation, regression and factor analyses. The multiple linear correlation (R) of O. 99 with a coefficient of determination of 0.97 was recorded. The regression analysis indicated that days to flowering, days to maturity, height at harvest, number of branches per plant, number of seeds per pod, nodulation and pod length contributed substantially to the variation due to regression. Only height at harvest and days to maturity were positively and significantly correlated with seed yield. Factor analysis produced a similar result to those of plant character correlation and regression analysis. The first four factors accounted for 82.53% of the variation in the dependence structure.